Role of Obesity on the Prognosis of Sudden Sensorineural Hearing Loss in Adults. (August 2015) - Hwang, Juen-Haur
Objective: To investigate the role of obesity/overweight on the prognosis of sudden sensorineural hearing loss (SSHL). Study Design: Retrospective cohort study. Setting: Outpatient department of a community hospital. Subjects and Methods: We collected 254 adult patients with SSHL from a community hospital. The odd ratios of body mass index (BMI) or obesity/overweight (BMI ≥25 kg/m 2 ) on the recovery of SSHL were evaluated with multivariate logistic regression analysis. Results: There were 120 (47.2%) patients in the nonobesity group (BMI <25 kg/m 2 ) and 134 (52.8%) patients in the obesity/overweight group (BMI ≥25 kg/m 2 ). The complete and partial recovery rates were 10.0% and 49.2% in the nonobesity group and 9.7% and 47.0% in the obesity/overweight group, respectively. Univariate logistic regression showed that BMI had no significant association with recovery of SSHL (odds ratio [OR] of complete and partial recovery versus no recovery = 1.04, 95% confidence interval [CI] = 0.965-1.113, P = .327). Multivariate logistic regression analysis also showed that BMI (OR = 1.04, 95% CI = 0.964-1.131, P = .292) was not significantly associated with the recovery of SSHL for all subjects, after adjusting for all considered variables. Also, obesity/overweight (BMI ≥25 kg/m 2 ) had no significant association with the recovery of SSHL. Conclusion: Obesity/overweight would appear to have no significant effect on the prognosis of SSHL.